(untitled) (Discourse of Law and Administration, 2025)
On 30 September 2018, the US, Canada and Mexico announced they had reached a trilateral free trade agreement in the renegotiation of the NAFTA, concluding more than 13 months of negotiations. The USMCA has been ratified by all three countries and has taken effect as of 1 July 2020. One of its crucial characteristics when it comes to workers’ rights is a facility-specific rapid response labour mechanism, which purpose is to ensure remediation of a “Denial of Rights” of free association and collective bargaining for workers at a Covered Facility, and to ensure that remedies are lifted immediately once a Denial of Rights is remediated (Annex 31-A “Facility-specific rapid response labor mechanism” between the US and Mexico of the USMCA’s Dispute Settlement chapter and separate Annex 31-B between Canada and Mexico). From 2021, the above-mentioned mechanism has been already used by the Department of Labor and the Office of the US Trade Representative on many occasions in order to protect workers’ rights under the USMCA. The author of this paper examines six first cases, namely: GM Silao, Tridonex, Panasonic, Teksid, VU Manufacturing and Saint Gobain. On such basis she draws conclusions regarding the effectiveness of the facility-specific rapid response labour mechanism.